-4m-16=4(1+2m)+8

Simple and best practice solution for -4m-16=4(1+2m)+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4m-16=4(1+2m)+8 equation:



-4m-16=4(1+2m)+8
We move all terms to the left:
-4m-16-(4(1+2m)+8)=0
We add all the numbers together, and all the variables
-4m-(4(2m+1)+8)-16=0
We calculate terms in parentheses: -(4(2m+1)+8), so:
4(2m+1)+8
We multiply parentheses
8m+4+8
We add all the numbers together, and all the variables
8m+12
Back to the equation:
-(8m+12)
We get rid of parentheses
-4m-8m-12-16=0
We add all the numbers together, and all the variables
-12m-28=0
We move all terms containing m to the left, all other terms to the right
-12m=28
m=28/-12
m=-2+1/3

See similar equations:

| 5-y=2+4y | | 2x-4÷2=6x+3 | | y-15.4=15.2 | | T=-4t^2+14t-6 | | 3x-9-6=4x+4 | | 6c-26=8c | | -3(x-1)=2(2-3x)+1 | | g/72-3/9=3/9 | | 50(3x)=2 | | 3e=3|4 | | z÷9=1.6 | | 15-4x=4(3-x)+2 | | 5(x+1)^1/4=10 | | 7/5=-4/5x | | 16(x+19)=23(x−19) | | 3(50x)=2 | | m-(-14)=-11 | | 27x=-6 | | 3z-11=7 | | 2/5(15x-10)=26 | | 11(x-2)=6(x-3)11 | | 5x-(3x+7)=83 | | 5b+9=-b-3 | | 3z/10-2=9 | | 45=3(j-53) | | 4b-8=13b-4-9b | | 4+3/5x=230 | | 45=3(j–53) | | x/7+9=7 | | 14=4k+6 | | 14=4k=6 | | 2(2x-4)-3x=8-3(2-5x) |

Equations solver categories